2019
DOI: 10.3389/fevo.2019.00253
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Adaptive Potential of Yellowtail Kingfish to Ocean Warming and Acidification

Abstract: but increasing in relative abundance between 1 and 21 dph at 25 • C. This suggests that this family line could perform better under future warming than in current-day conditions. Our results provide the first preliminary evidence of the adaptive potential of a large pelagic fisheries species to future ocean conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…At the time of spawning, the water was at 18.2 °C and had a pH of 7.91 (pCO 2 = 589 µatm). Parentage analysis showed that 5 females and all 10 males contributed to the spawning (Munday et al, 2019). Eggs were collected on 24th January 2017 from the overflow of each of four tanks, approximately 12 h post fertilization.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of spawning, the water was at 18.2 °C and had a pH of 7.91 (pCO 2 = 589 µatm). Parentage analysis showed that 5 females and all 10 males contributed to the spawning (Munday et al, 2019). Eggs were collected on 24th January 2017 from the overflow of each of four tanks, approximately 12 h post fertilization.…”
Section: Methodsmentioning
confidence: 99%
“…Variation for plasticity among genotypes offers a target for selection in a warming environment if the variation of traits is heritable (Chevin et al, 2010;Munday et al, 2017Munday et al, , 2019, and is an important component of the adaptive capacity of populations and species. Already during recruitment of juvenile sporophytes for experiment 2, we observed that one out of ten genetic lines recruited more sporophytes at 15 • C than at 5 • C (Supplementary Figure S4 and Supplementary Table S3).…”
Section: Genetic Variation For Plasticitymentioning
confidence: 99%
“…Third, which partially overlaps with transgenerational effects, is the potential role of genetic adaptation in responses to marine climate change. Experiments from this decade revealed that there may be some potential for adaptation (Welch and Munday, 2017;Jury et al, 2019;Munday et al, 2019), although trade-offs are likely (Kelly et al, 2016). Experimental testing of evolutionary processes on marine organisms has been historically limited, due to methodological limitations and a lack of model organisms (Munday et al, 2013).…”
Section: Discussionmentioning
confidence: 99%